Variations of vitamins (A, C and E) and MDA in apricots dried in IR and microwave - Karatas, Fikret; Kamisli, Fethi (Elsevier Sci Ltd, 2007)
In this study, variations of vitamins (A, C and E) and malondialdehyde (MDA) with moisture removals were investigated in apricot samples in different ripeness namely near-ripe and ripe apricots that were dried in infrared and microwaves driers. For two drying systems, the values of vitamins (A and E) and MDA in the ripe apricot were observed to be higher than those in the near-ripe apricot samples at all moisture removals. The values of vitamins (A, C and E) and MDA in apricot samples dried in the microwave drier were found to be larger than those in apricot samples dried in infrared. Infrared and microwave driers were compared one another in terms of less losses of vitamins and MDA, rate of drying and preservation of original color of apricot. It was concluded that microwave drier is more effective than IR drier in terms of less losses of vitamins, rate of drying and preservation of original color of apricots. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: apricot; drying; antioxidant vitamins and MDA